Doctoral students' agency as second language writing teachers: The quest for expertise. (December 2018) - Christiansen, M. Sidury; Du, Qian; Fang, Ming; Hirvela, Alan
Abstract: Since the 1980s, when the field of second language writing (SLW) began to establish itself as a discipline in its own right, much has been learned about SL writers and their writing. However, there has been relatively little focus on teachers of SLW, including their experiences with teacher agency. In the study reported here, we focus on a group that is even less examined: graduate teaching assistants assigned to teach writing courses in English as a Second Language (ESL) programs. More specifically, we look at three international graduate teaching assistants and their teacher agency, which we explored through their participation in a small professional learning community and in relationship to their quest to develop expertise as SLW teachers. Our findings illustrate how understanding of teacher agency can be enhanced by making connections between expertise and agency, particularly adaptive expertise.